PENGARUH LEADER MEMBER EXCHANGE TERHADAP KEPUASAN DENGAN LOCUS OF CONTROL INTERNAL SEBAGAI VARIABEL MODERASI - , Meyke Mirabillya; , Prof. Dr. Djamaludin Ancok, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to measure the influence of Leader Member Exchange (LMX) on job satisfaction with internal Locus of Control (LOC) as a moderating variable. There are three variables in this study: (1) LMX as the independent variable, (2) job satisfaction as the dependent variable, (3) internal LOC as a moderating variable. The hypotheses of this research are: (1) LMX has a significant relationship with job satisfaction, (2) internal LOC has a significant relationship with job satisfaction, (3) LMX relationship with job satisfaction is moderated by internal LOC. This research surveyed 49 employees of PT. SKG, the company is a subsidiary of the leading developers in Indonesia named Agung Sedayu Group. LMX measured using the LMX 7 questionnaires developed by Graen, Novak, and Somerkamp (as written by Collins, 2007). Job Satisfaction measured using Minnesota Satisfaction Questionnaire (MSQ) short form developed by Weiss, Cavis, England, and Lofquist (as written by Newby, 1999). And, internal LOC was measured using a scale of Internal-External Locus of Control developed by Rotter (as written by Coit, 2006). Data were analyzed using the method of simple and multiple regression analysis. Simple regression analysis was used to analyze: (1) the influence of LMX on job satisfaction, (2) the influence of internal LOC on job satisfaction. The results of simple regression analysis showed that LMX significantly influence job satisfaction, while the internal LOC not significantly influence job satisfaction. Multiple regression analysis used to test the influence of LMX on job satisfaction with internal LOC as a moderating variable. The results of multiple regression analysis showed that after an internal LOC factors used as moderating variables, the influence of LMX on job satisfaction were significant. Based on these results, it showed that the influence of LMX on job satisfaction were significant after an internal LOC was placed as a moderating variable.